Kahulugan at Kairalan - Mabaquiao Jr., Napoleon M. (Social Science Diliman: A Philippine Journal of Society and Change, 2007)
This essay is a general analysis of how certain ways of understanding the meaningfulness of words (or how certain ways of explaining how words acquire meaning) can affect beliefs regarding what exists in the world. The main focus is the philosophical controversy regarding the meaning of general terms. Accordingly, traditional approaches to this issue disagree on the kinds of entities that ought to exist in order for these terms to be meaningful. The author's analysis of this controversy proceeds as follows. First, it is explained how philosophers classify entities into several kinds and how they generally argue in support of their preference for certain types of entities over others. This discussion also distinguishes the method of linguistic analysis from other philosophical methods in dealing with ontological issues (or issues concerning existence). Then, the claims and arguments of the traditional accounts of the meaning of general terms are presented and explained. Lastly, these accounts are criticized using the perspective of the use theory of meaning of the philosopher Ludwig Wittgenstein. Among others, it is shown that the said accounts all assume the referential theory of meaning, which Wittgenstein strongly criticizes. At the latter part, the author also gives his reflections, in the light of this discourse, on the concept of Filipino as it relates to the issue of national identity.